Evaluasi Implementasi Knowledge Management System Penerapan E-Learning di Sekolah Menengah Atas - Adelia Alvi Yana; Astrilyana; Nunung Hidayatun; Sinta Nurhayati (LPPM STMIK ANTAR BANGSA, 2019)
Abstract— Knowledge Management system is an organization of knowledge that is owned by individuals in an organization. With Knowledge Management, an individual's knowledge will become an organization's knowledge so that it is beneficial for an organization. With the many Knowledge Management systems that have been implemented in several organizations in Indonesia, the researchers want to evaluate the implementation of Knowledge Management systems in the learning process by e-learning in public high schools. The background of this study is to analyze the evaluation of learning outcomes in e-learning as a medium in the learning process in public high schools. In this study, using the model applied by Tiwana regarding the implementation of knowledge management by referring to the evaluation phase based on the measurement of performance evaluation. The research method used is quantitative evaluative with purposive sampling technique.